Colombia : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses Colombia's 2005 Article IV Consultation, Fourth Review Under the Stand-By Arrangement (SBA), and Requests for Waiver of Nonobservance of Performance Criteria. Real economic growth in Colombia recovered to 4 percent a year in 2003-04. The national unemployment rate declined from 20 percent at end-2000 to 12 percent at end-2004. The health of the financial system continued to improve. The solvency and profitability of the banking system have recovered, reflecting economic growth, a successful recapitalization scheme, and improved supervision.